PENAMBAHAN AIR KAPUR DAN BAYAM PADA PAKAN UNTUK MEMPERSINGKAT DURASI MOULTING KEPITING BAKAU (SCYLLA SERRATA) JANTAN - DWI AGUS P, ANDIKA (Universitas Negeri Surabaya, 2013)
One of the soft shell crab production technology is using spinach extract to stimulate moulting. Spinach extract contains phytoecdysteroid, a substance which is well known to stimulate moulting in mudcrabs. Ecdysteroid synthesis is a process that requires the presence of Ca2+ as a trigger. The purpose of this study were to determine the effect of various concentrations of lime water and spinach on feed to the duration of moulting and get a combination of lime water and spinach concentration that produces the shortest duration of moulting on male mudcrabs (Scylla serrata). This research used Randomized Completely Block Design (RCBD) with factorial pattern that consists of factor I: 5 levels of lime water concentrations (0, 2, 3, 4, dan 5 ml) and factor II: 5 levels of spinach concentrations (0, 10, 20, 30, dan 40 g) with 3 repetitions. Data obtained were analyzed by Friedman test. The results showed  that the addition of  lime water and  spinach combinations with various concentrations on the feed have  different effects to the duration of moulting of mudcrabs. The shortest duration of moulting was obtained in the treatment of  A4B40 formula, add with 4 ml of  lime water and 40 g of spinach to th feed,  in average of 20 days.   Key words: ecdysteroid; lime water; Ca2+; spinach; “moulting” duration; mudcrab (Scylla serrata)